Chemical and Structural Analysis of Rocks Using X-ray Fluorescence and X-ray Diffraction Techniques - Mohammed M. Sabri (ARO-The Scientific Journal of Koya University, 2020)
Rock examinations for mining and commercial use are a vital process to save money and time. A variety of methods and approaches have been used to analyze rocks and among them, X-ray fluorescence (XRF), and X-ray diffraction (XRD) techniques proved to be an accurate method. This research was conducted to evaluate the utility and reliability of XRF and XRD to analyze the major and trace elements of rocks as well as their crystalline structures. Results showed that XRF and XRD techniques are fast and reliable, nondestructive and non-invasive analytical tools for mineral analysis, particularly for rocks. For this purpose, the analysis of 28 samples of rocks, which collected from three different places of Kurdistan region-Iraq, is reported. These places are Haybat Sultan (HS) region in Koya city as well as TaqTaq (TA) and Garmuk (GT) district nearby Koya city. Throughout this analysis, 34 major and trace elements were detected in the rocks collected from HS region, whereas forty major and trace elements were detected in the rocks collected from TA district and GT district. In addition, it was found that the structures of these rocks were crystalline in nature. This was proved through the value of diffracted angle and it was found that the majority of these rocks are oxides. The external view (the appearance) of all collected rocks was also discussed and it was found that each rock consists of a variety of minerals which will be the reason that each rock has a specific color.